STRATEGI PENGOPTIMALAN PAKAN FERMENTASI DENGAN FORMULASI LIMBAH AMPAS TAHU TERHADAP PRODUKSI BUDIDAYA LELE DI DESA CANDISARI KECAMATAN SAMBENG KABUPATEN LAMONGAN - Wachidatus Sa'adah; Wulan Sari (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2018)
This research was conducted with the aim to know the technical manufacture of fermented feed with the formulation of waste of tofu and optimization strategy of making to the production of catfish culture. This research was conducted in Candisari Village, Sambeng Sub-district, Lamongan District. The method used in this research is qualitative method. From the result of the research that the making of fermented feed with the formulation of waste of tofu waste includes preparation method, materials of manufacture and process of manufacture, while the optimization strategy is (a) increasing production of fermented feed with the formulation of waste of tofu waste; (b) business development and introduction to the community, that fermented feed can increase fish farming production; (c) increasing the production of fermented feeds into products of sale value; (d) optimizing the waste of tofu waste into alternative feed.Keywords : Feed, Fermentation, Tofu, SWOT Analysis